The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1002/ldr.3872
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the diversity of the soil microbial community and structure under various categories of degraded wetland in Sanjiang Plain, northeastern China

Abstract: Understanding the changes in microbial community composition in wetlands affected by different types of degradation can help enrich theoretical knowledge about wetland degradation. However, studies of the relative role of microorganisms under different types of degradation of wetlands are rare in wetland ecology. Because of agricultural development, a large volume of groundwater has been extracted from the Sanjiang Plain over the last few decades, which has caused wetland degradation.To provide information for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 89 publications
1
26
0
Order By: Relevance
“…Soil microbes play a vital role in many ecological processes of wetlands and are essential for maintaining ecosystem functions and stability (Wu et al, 2021). The microbial community is closely associated with ecological functioning of soil microbes, because of the diverse functions provided by the different microbial species (Crowther et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Soil microbes play a vital role in many ecological processes of wetlands and are essential for maintaining ecosystem functions and stability (Wu et al, 2021). The microbial community is closely associated with ecological functioning of soil microbes, because of the diverse functions provided by the different microbial species (Crowther et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The microbial community also contributes to soil structure regulation, soil formation and plant productivity (Zhang et al, 2013;Gao et al, 2021). The soil microbial community is sensitive to variation in soil physicochemical properties and can serves as an indicator of soil quality (Yu et al, 2012;Wu et al, 2021). In reverse, changes in microbial community can also provide feedback to ecosystem functions and may offer an opportunity to mitigate the impact of ecosystem alterations induced by human disturbance and environmental variation (Huang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The deterioration of soil habitat caused by grassland degradation is mainly due to the destruction of soil structure and the sharp loss of soil nutrients, especially soil nitrogen and carbon, which destroy the soil biological system and the growth environment of plant roots ( Liu et al, 2020 ; Sun et al, 2020 ; Wu et al, 2021 ). For example, a study in the Qinghai-Tibet Plateau found that the nitrogen content in the soil decreased by 49% after the degradation of grassland ( Dong et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%